Survey Study of ESP Learning Needs at the Islamic Religious Education Study Program of Tarbiyah Faculty of IAIN Bengkulu - Syamsul Rizal; Maryam Maryam (Ta'dib, 2020)
This study aimed to determine the needs of non-English Study Program students. Quantitative and survey methods were applied in this study. A questionnaire through the Graves model analysis consisting of student profile analysis, Target Situation Analysis (TSA), Current Situation Analysis (CSA), and Learning Situation Analysis (LSA) were the instruments used in collecting the data. Participants were the third-semester students of the Islamic Religious Education Study Program at Tarbiyah and Tadris Faculty of IAIN Bengkulu in 2018 to 2019 academic year. In determining the participants, the writers applied a simple random sampling technique. There were 37 students from a total population of 150 students. The data were analyzed using descriptive statistical analysis, namely by calculating percentage (%) and classified data so that the needs of students in learning English could be identified. The findings were (1) the ESP approach was the right approach to be applied in learning English at IAIN Bengkulu based on the students’ age and experience in learning English,  (2) the gap between the targeted needs by the campus and the students’ English skills was less, (3) the gap between what students needs and the material in the ESP English textbook was in category desire, and (4) the topic of reading comprehension text was directly related to the study of Islamic Religious Education as a student’s area of ​​expertise.